Karakteristik Pasien Stroke Hemoragik Di RSUD Raden Mattaher Jambi Tahun 2017-2021 - Ega Benita; Mirna Marhami Iskandar; Ima Maria; Nidia Suriani; Armaidi Darmawan (Journal of Medical Studies, 2024)
ABSTRACT Background: Hemorrhagic stroke is spontaneous bleeding in the parenchyma or intracerebral brain, subarachnoid space, or intraventricular space due to sudden rupture of intracranial blood vessels. Hemorrhagic strokes account for 15% of total strokes and the burden of disability is greater than ischemic strokes. Aim: To find out the characteristics of hemorrhagic stroke patients at Raden Mattaher Jambi Hospital in 2017-2021. Methods: This type of research uses descriptive research. The sample of this study was hemorrhagic stroke patients at Raden Mattaher Hospital Jambi in 2017- 2021 by looking at the patient's medical records and fulfilling the inclusion criteria. Results: The largest age group was the late elderly (56-65 years), dominated by women. The most common type of bleeding was ICH and the location was deep cerebral. The most common risk factors were emergency hypertension and grade 2 hypertension. Most patients did not have diabetes mellitus, or dyslipidemia, and did not smoke. Conclusion: Hemorrhagic stroke is most common in the late elderly group (56- 65 years), the majority are women, the most common type of bleeding is ICH, the most common location is deep cerebral, and hypertension is the main risk factor. Keywords: Hemorrhagic stroke, Raden Mattaher Hospital ABSTRAK Latar belakang: Stroke hemoragik adalah perdarahan spontan pada parenkim atau intraserebral otak, ruang subarachnoid, atau ruang intraventrikular akibat pecahnya pembuluh darah intrakranial secara tiba-tiba. Stroke hemoragik menyumbang 15% dari total stroke dan beban kecacatan lebih besar daripada stroke iskemik. Tujuan: Mengetahui karakteristik pasien stroke hemoragik di RS Raden Mattaher Jambi tahun 2017-2021. Metode: Jenis penelitian yang digunakan adalah penelitian deskriptif. Sampel penelitian ini adalah pasien stroke hemoragik di Rumah Sakit Raden Mattaher Jambi tahun 2017-2021 dengan melihat rekam medis pasien dan memenuhi kriteria inklusi. Hasil: Kelompok umur terbanyak adalah lansia akhir (56-65 tahun) yang didominasi oleh perempuan. Jenis perdarahan yang paling umum adalah ICH dan lokasinya di serebral dalam. Faktor risiko yang paling umum adalah hipertensi darurat dan hipertensi grade 2. Sebagian besar pasien tidak menderita diabetes melitus, dislipidemia, dan tidak merokok. Kesimpulan: Stroke hemoragik paling banyak terjadi pada kelompok lansia akhir (56-65 tahun), mayoritas wanita, jenis perdarahan tersering adalah ICH, lokasi terbanyak serebri dalam, dan hipertensi merupakan faktor risiko utama. Kata Kunci: Stroke Hemoragik, RSUD Raden Mattaher